Ameliorative effect of trigonelline in restraint stress-induced behavioral alterations in mice - Prabhjot Kaur, Thakur Gurjeet Singh, Amarjot Kaur, Sonia Dhiman, Sandeep Arora (Journal of Applied Pharmaceutical Science, 2021)
Physical activity and stress are environmental modifiers for various neurodegerative disorders. The consistent psychological restraint stress has impacts the neurobiological changes like brain shrinkage or inhibiting the neurogenesis, mainly affecting the hippocampal CA3 region and exacerbating various neuropathologies. Therefore, stress directly modulates the pathology and neurobiology of human beings. The current research was designed to evaluate the anti-stress ability of trigonelline in behavioral and biochemical changes caused by restraint stress in mice. Various stressful stimuli have affected numerous physiological-based physical processes. There is no particular pharmacotherapy available to date which can count as stress reduction therapy. In the present study, female mice were subjected to restraint stress in flat bottomed restrainers with dimensions of 1.5″ dia × 4″, for 3.5 hours. The behavioral alterations by inducing restraint test were analyzed by using a battery of tests like social interaction, hole board, open field test, and elevated plus maze. The investigation of inducing restraint stress was processed which further resulted in exploratory behavior of grouped mice. Social behavior was measured by exploring the number of head dips and frequency of rearing in the hole board test. Apart from this, biochemical parameters, such as thiobarbituric acid reacting substance (TBARS), catalase (CAT), reduced glutathione (GSH) levels, myeloperoxidase, and superoxide dismutase (SOD), were analyzed. Mice treated with trigonelline (25 and 50 mg/kg, i.p.) significantly (p < 0.05) and dose-dependently attenuate stress-induced behavior and oxidative alterations, when compared to the stress control group. The current study confirmed the ameliorating effect of the trigonelline in restraint stress effect by attenuating the increased levels of MPO (Myeloperoxidase) and TBARS as stress parameters and enhancing the levels of protective enzymes such as GSH, SOD, and CAT. Hence, the study proposed a protective mechanism of trigonelline ameliorating stress by modulating the nuclear factor erythroid 2-related factor 2 pathways and oxidative stress.
Keywords: Neurobiology, trigonelline, restraint stress, biochemical parameters, diazepam, Nrf2, myeloperoxidase.